Wind Power Generation Scenarios in Lebanon - Kassem, Y.; Gokcekus, H.; Camur, H.; Abdelnaby, A. H. A. (Engineering, Technology & Applied Science Research, 2022)
Renewable energy in terms of solar and wind energy can be an essential part of Lebanon’s strategies to add new capacity, increase energy security, address environmental concerns, and resolve the electricity crisis. In this regard, there is an urgent need to develop road maps in order to reduce the effect of global warming and enhance sustainable technological development for generating clean power in the country. Therefore, the present paper evaluates Lebanon’s wind energy generation potential as an alternative solution to supply electricity to households in various locations distributed over Lebanon. In the present study, the measured data are used to evaluate the wind energy potential in Lebanon and to find suitable locations to install wind farms in the country. Accordingly, the results demonstrated that Ain ed Dabaa is the most suitable location for the installation of a wind farm. Moreover, the study aims to develop a wind energy cost analysis techno-economic model for eight conventional wind turbines and a Barber wind turbine, which was found to be very competitive. Consequently, this study showed that the implementation of a wind turbine could provide clean, economical, and continuous production of electricity in countries that suffer from daily blackouts.